Basic surgical skills and techniques - Kumar Jain, Sudhir MS FRCS (Edinburgh) FACS FICS Professor; David L. Stoker; Raman Tanwar; ; contributors Beryl Antoinette De Souza MD, David L Stoker MD FRCS (Edinburgh), Gemma Conn MD, Raman Tanwar, Sudhir Kumar Jain MS FRCS (Edinburgh) FACS FICS (India : Jaypee Brothers Medical Publishers, 2013)
The second edition of Basic skill and techniques represents a major advance over its firts edition. This highly acclaimed book comprehensively covers the essentials of a bright surgial career. The book has been widely accepted due to its simple yet thoroungh presentation. The second edition to this book brings a welcome change in the form of improved readability, enhanced figures and additions of four new chapters that cover basic surgical procedures, instruments and latest advances in the field of surgery.
Contents 1. Scrubbing, gowning and gloving techniques Suchir Kumar Jain, david L. Stoker 2. Knot tying techniques Sudhir Kumar Jain, David L Stoker 3. Wound closure techniques Sudhir Kumar Jain, David L Stoker 4. Surgery of common skin lesions under local anaesthesia Sudhir Kumar Jain, Beryl Antoinette De Souza 5. Sutures in surgery Sudhir Kumar Jain, David L Stoker 6. Patient positioning during surgery Sudhir Kumar Jain, David L Stoker 7. Anastomosis in surgery Sudhir Kumar Jain, Raman Tanwar 8. Art of instrument handling Sudhir Kumar Jain, David L Stoker Y otros once capítulos más Index
Incluye Contents
Incluye Index
Keywords: CIRUGÍA; TÉCNICAS QUIRÚRGICAS; SURGICAL